Autism spectrum disorder in individuals with anorexia nervosa and in their first- and second-degree relatives: Danish nationwide register-based cohort-study. (May 2015) - Koch, Susanne V.; Larsen, Janne T.; Mouridsen, Svend E.; Bentz, Mette; Petersen, Liselotte; Bulik, Cynthia; Mortensen, Preben B.; Plessen, Kerstin J.
Abstract : Background: Clinical and population-based studies report increased prevalence of autism spectrum disorders (ASD) in individuals with anorexia nervosa and in their relatives. No nationwide study has yet been published on co-occurrence of these disorders. Aims: To investigate comorbidity of ASD in individuals with anorexia nervosa, and aggregation of ASD and anorexia nervosa in their relatives. Method: In Danish registers we identified all individuals born in 1981–2008, their parents, and full and half siblings, and linked them to data on hospital admissions for psychiatric disorders. Results: Risk of comorbidity of ASD in probands with anorexia nervosa and aggregation of ASD in families of anorexia nervosa probands were increased. However, the risk of comorbid and familial ASD did not differ significantly from comorbid and familial major depression or any psychiatric disorder in anorexia nervosa probands. Conclusions: We confirm aggregation of ASD in probands with anorexia nervosa and in their relatives; however, the relationship between anorexia nervosa and ASD appears to be non-specific.